An Exploratory Study on Quality Improvement and Effective Management Among Hospital Industry in Puducherry Region - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
The purpose of quality management in hospitals is to establish a system that measures and manages patient in a way that provides the optimal care for all patients. This study empirically explores the relationship between hospital quality management and service quality performance in Puducherry region. The objectives of this quality standard are 1) to provide an implementation mechanism that will facilitate the reliable administration of prophylactic antimicrobial agents to patients undergoing operative procedures in which such a practice is judged to be beneficial and 2) to provide a guideline that will help local hospital committees formulate policies and set up mechanisms for their implementation. The research reveals strong relationships between hospital service quality performance and the analysis of service process and workforce development. The data also indicate that medical technology investment alone does not contribute to a significant improvement in hospital service quality. It is the analysis of the health service process information collected using advanced technology that considerably contributes to health service quality improvement. In addition, the study shows that organizational cooperation, workforce development, medical technology investment, and information/process analysis mediate the relationship between health service quality and top management leadership.